Transfer of tylosin across the H2O/1,2-dichloroethane interface. Analysis of degraded product in acid solutions - Fernández, Ricardo Ariel (2010)
Cyclic voltammetry applied to liquid/liquid interfaces and nuclear magnetic resonance spectroscopy were used to analyze the stability of tylosin A in aqueous solutions in acid conditions. Cyclic voltammetry was employed to characterize the charge transfer processes for tylosin A and tylosin B across the H2O/1,2-dichloroethane interface. Electrochemical study includes the transfer potential dependence of pH value, the elucidation of the mechanism of transfer using mechanical control of convective flux, and the determination of partition coefficient values and diffusion coefficient values employing the change of voltammetric current with external parameters. Degradation process of tylosin A was monitored and tylosin B or desmycosin was isolated and then identified and characterized by nuclear magnetic resonance spectroscopy and electrochemical techniques.